Role of Perinatal Inflammation in Neonatal Arterial Ischemic Stroke - Giraud, Antoine; Guiraut, Clémence; Chevin, Mathilde; Chabrier, Stéphane; Sébire, Guillaume (Frontiers in Neurology, 2017)
Based on the review of the literature, perinatal inflammation often induced by infection is the only consistent independent risk factor of neonatal arterial ischemic stroke (NAIS). Preclinical studies show that acute inflammatory processes take place in placenta, cerebral arterial wall of NAIS-susceptible arteries and neonatal brain. A top research priority in NAIS is to further characterize the nature and spatiotemporal features of the inflammatory processes involved in multiple levels of the pathophysiology of NAIS, to adequately design randomized control trials using targeted anti-inflammatory vasculo- and neuro-protective agents.